MAKNA REPRESENTAMEN KENDARAAN PADA FILM ANIMASI ANAK CAR TOONS COMPILATION: KAJIAN SEMIOTIKA C.S. PEIRCE - Soekma Yeni Astuti; Yanuaresti Kusuma W. (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
Car Toons Compilation is an animated film by the YouTube channel First Toons which contains a compilation of episodes of Car Toons, including A Tow Truck, A Water Truck, and A Tractor. Car Toons tells a different story in each episode but still includes car elements. This study aims to discuss the semiotic understanding of the animated film by using Peirce's semiotic theory, especially icons, indexes, and symbols. The method used in this study is a qualitative method with descriptive analysis, which emphasizes the process of semiosis with the meaning of the relationship between signs or representamen in the elements of animated films and their benefits for children. The study results show that the animated films A Tow Truck, A Water Truck, and A Tractor have imaginary icons, namely visuals based on similarities to reality. The Tow Truck's indexicality as a saviour for a breaking car has a symbol of a towing tool that has a tip like a fishing hook on the back of the truck. The indexicality of the Water Truck is used to save alive whales even though they are on land. The blue object is a symbol of water. Tractor truck indexicality that agricultural land can be planted due to tractor services, its symbolism is that the animation of land with plants is agricultural land. Based on this discussion, the meaning of representamen provides benefits for children in the form of understanding the types of trucks and their uses.